"Ask a Doctor About Coronavirus": How Physicians on Social Media Can Provide Valid Health Information During a Pandemic - Furstrand, Dorthe; Pihl, Andreas; Orbe, Elif Bayram; Kingod, Natasja; Søndergaard, Jens (JMIR Publications, 2021)
In the wake of the COVID-19 pandemic, the information stream has overflowed with accurate information, misinformation, and constantly changing guidelines. There is a great need for guidance on the identification of trustworthy health information, and official channels are struggling to keep pace with this infodemic. Consequently, a Facebook group was created where volunteer medical physicians would answer laypeople's questions about the 2019 novel coronavirus. There is not much precedence in health care professional-driven Facebook groups, and the framework was thus developed continuously. We ended up with an approach without room for debate, which fostered a sense of calmness, trust, and safety among the questioners. Substantial moderator effort was needed to ensure high quality and consistency through collaboration among the presently >200 physicians participating in this group. At the time of writing, the group provides a much-needed service to >58,000 people in Denmark during this crisis.